CIRI-CIRI DISLEKSIA PADA ANAK USIA DINI - Iza Syahroni; Wasilatur Rofiqoh; Eva Latipah (Department of Early Childhood Education, STKIP Bina Bangsa Getsempena, 2021)
Dyslexia is a type of learning difficulty in children in the form of reading disabilities, symptoms that are not caused by the ability of sight, hearing, intelligence, or skills in languagee, but rather to disturbances in the brain processes when processing the information it receives. The factors that couse dyslexia, are phenoological problems, educational factors, psychological factors, and biological factors. As for the characteristics of dyslexia, among others: symptoms of dyslexia in pre-school: 1), loves to mix up words and phrases, 2), difficulty learning the repetition of sounds (rhymes) and rhythms, 3) it’s hard to remember names, 4) late development in language, 5) happy to read a book, but not interested in words or letters, 6 it’s hard to dress. The characteristics of dyslexia at elementary school age: 1) difficulty reading and speeling, 2) often confused letters and numbers, 3) it’s hard to remember names, 4) difficult to understand the writing he read, 5. Slow at writing, 6 difficulty concentrating, 6) difficulty concentrating, 7) it’s hard to tell right and left, or the order of the week, 8) low self-esteem, and 9) still have difficulty in dressing. Abstrak Disleksia adalah jenis kesulitan belajar pada anak berupa ketidak mampuan membaca, gejala yang tidak disebabkan oleh kemampuan penglihatan, pendengaran, intelegensia, atau keterampilannya dalam berbahasa, melainkan lebih kepada gangguan dalam proses otak ketika mengolah informasi yang diterimanya. Faktor-faktor penyebab disleksia , adalah masalah fenoologi, faktor pendidikan, faktor psikologis, dan faktor biologis. Adapun ciri-ciri disleksia di antaranya: Ciri-ciri disleksia pada pra-sekolah: (1) Suka mencampur adukkan kata-kata dan frasa (2) Kesulitan mempelajari pengulangan bunyi (rima) dan irama (ritme), (3) Sulit mengingat nama, (4) Perkembangan dalam berbahasa yang terlambat, (5) Senang dibacakan buku, tetapi tidak tertarik dengan kata-kata atau huruf, (6) Sulit untuk berpakaian. Adapun ciri-ciri disleksia diusia sekolah dasar: (1) Sulit membaca dan mengeja, (2) Sering tertukar huruf dan angka, (3) Sulit mengingat alfabet atau mempelajari tabel, (4) Sulit mengerti tulisan yang ia baca, (5) Lambat dalam menulis, (6) Sulit konsentrasi, (7) Susah membedakan kanan dan kiri, atau urutan dalam sepekan, (8)Percaya diri yang rendah, (9) Masih tetap kesulitan dalam berpakaian. Kata Kunci: Disleksia, Kesulitan Belajar, dan Pendidikan